2020
DOI: 10.2196/17085
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Secure Apps for Daily Clinical Use by German Orthopedic Surgeons: Searching for the "Needle in a Haystack"

Abstract: Background It is undeniable that appropriate smartphone apps offer enormous opportunities for dealing with future challenges in orthopedic surgery and public health, in general. However, it is still unclear how the apps currently available in the two major app stores can be used in daily clinical routine by German orthopedic surgeons. Objective This study aimed to gain evidence regarding the quantity and quality of apps available in the two major app st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…This study demonstrated the feasibility of using a mobile app to monitor the recovery status of patients with drains and to assist patients and caregivers in detecting abnormalities in a timely manner. Remote apps could support self-care and allow close follow-up [32][33][34]. We also identified an unexpected reduction in the rates of hospital return and readmission in the SurgCare group (6.4%) compared with the conventional group (25.9%) (P=.02).…”
Section: Discussionmentioning
confidence: 81%
“…This study demonstrated the feasibility of using a mobile app to monitor the recovery status of patients with drains and to assist patients and caregivers in detecting abnormalities in a timely manner. Remote apps could support self-care and allow close follow-up [32][33][34]. We also identified an unexpected reduction in the rates of hospital return and readmission in the SurgCare group (6.4%) compared with the conventional group (25.9%) (P=.02).…”
Section: Discussionmentioning
confidence: 81%
“…This study demonstrated the feasibility of using a mobile app to monitor the recovery status of patients with drains and to assist patients and caregivers in detecting abnormalities in a timely manner. Remote apps could support self-care and allow close follow-up [ 32 - 34 ]. We also identified an unexpected reduction in the rates of hospital return and readmission in the SurgCare group (6.4%) compared with the conventional group (25.9%) ( P =.02).…”
Section: Discussionmentioning
confidence: 99%
“…Eine der größten Herausforderungen für deutsche Ärzte in O und U stellt bereits die Suche nach der passenden App dar. Die Unübersichtlichkeit und Dynamik der App Stores lässt die Suche nach der passenden App wie die Suche nach der "Stecknadel im Heuhaufen" erscheinen [14]. Lösungsansätze können die stetig ansteigende Zahl von App-Store-basierten Reviews kommerziell erhältlicher Apps darstellen, die sich kritisch mit den derzeit verfügbaren Apps auseinandersetzen sowie inhaltliche und methodische Ansätze für die persönliche App-Suche liefern [17].…”
Section: Sinnvolle Anwendungenunclassified